Faith and Ethnicity : Volume 2 - Borght, van der,; Keulen, Dirk van,; Brinkman, Martien, (Studies in Reformed Theology;, 2002)
In writing 'In Christ there is neither Jew nor Greek', the apostle Paul touched on a topic that still is hotly debated among Christians today: the relationship between faith and ethnicity. The Reformed Chuches, usually organised along regional or national lines, are no exception and wrestle world-wide with the issue. This volume offers more traditional Western, mostly European perspectives, exploring Western and Eastern European and North American contexts. Hermeneutics, church order and ecumenical aspects complement the theme. This and the previous volume of Studies in Reformed Theology contain contributions to the fourth international conference of the International Reformed Theological Institute (IRTI), held in Princeton, N.J., U.S.A. (2001), on the theme of Faith and Ethnicity.